2011
DOI: 10.1590/s0066-782x2011001500019
|View full text |Cite
|
Sign up to set email alerts
|

Angiogênese coronariana como resposta endógena da isquemia miocárdica no adulto

Abstract: The process of angiogenesis involves a complex sequence of stimuli and integrated responses, such as stimulation of endothelial cells (ECs) for their proliferation and migration, stimulation of the extracellular matrix (ECM) for the attraction of pericytes and macrophages, stimulation of smooth muscle cells for their proliferation and migration, and formation of new vascular structures. Angiogenesis is mainly an adaptive response to tissue hypoxia and depends on the accumulation of the hypoxia-inducible factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Other authors have mentioned that interstitial inflammatory immuno-infiltrates are present in the ischemic heart disease and in myocardium of LPS-induced sepsis (Cuenca et al, 2006;Lorier et al, 2011). This study suggests that Mps obtained from in vivo LPS-treated mice are able to up-regulate its own production of NO as well as VEGF-A levels, MMP-9 expression and activity and new blood vessel formation in heart tissue.…”
Section: Discussionsupporting
confidence: 50%
“…Other authors have mentioned that interstitial inflammatory immuno-infiltrates are present in the ischemic heart disease and in myocardium of LPS-induced sepsis (Cuenca et al, 2006;Lorier et al, 2011). This study suggests that Mps obtained from in vivo LPS-treated mice are able to up-regulate its own production of NO as well as VEGF-A levels, MMP-9 expression and activity and new blood vessel formation in heart tissue.…”
Section: Discussionsupporting
confidence: 50%
“…Recruitment of cEPCs, as well as proliferation and survival of endothelial cells and vascular smooth muscle cells were necessary for the formation of vascular sprout and lumen. Usually, the high number or density of these cells is indicative of angiogenesis [14]. Our results showed that promoting angiogenesis in ischemic myocardial tissues could be a possible mechanism of the cardioprotective effects of acupuncture in MI cases.…”
Section: Discussionmentioning
confidence: 56%
“…Our data indicated a marked increase in VEGF genes expression as a result of EA treatment. Angiogenesis is known as an adaptive response to tissue hypoxia in ischemic myocardial areas, and it is considered a target in treating ischemic diseases, including myocardial ischemia [14], [24]. Acupuncture treatment has also proven to alleviate ischemic symptoms in other types of ischemic diseases via promoting angiogenesis [25], [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations